探讨新加坡1980年代《宗教知识》的有效性 ：以《佛学》为个案研究 = The effectiveness of "religious knowledge" in 1980's Singapore education on cultivating moral values : on "Buddhist studies" as a case study - 李虹霖 Lee, Honglin (2015)
1965年独立后，新加坡随即面临建立一个新兴国家的艰难任务，其传统和文化更备受现代化的挑战。人民行动党的首要任务便是带领国民远离先前动荡不安的年代，建立一个不分彼此或存有偏见、使各种族和睦共处的国家意识。教育因此成为国家达到此目的的最佳途径。除了强调科技和技能培训，此管道亦可作为品格与公民课程中培养人民素质不可忽略的重要部分。1984年，新加坡政府在各中学学府开始实行《宗教知识》，作为道德教育的新课程。这项新政策规定中学三年级的学生必须修读两年的《宗教知识》，并提供六种宗教或哲学系统的知识，包括佛教、儒家思想、基督教、回教、兴都教以及锡克教。学生必须从中任选一门知识加以修读。然而，在计划实行六年后的1989年，新加坡政府就宣布《宗教知识》将逐步终止教导这门必修课。 对上述所谈到的现象，本文将通过新加坡社会和经济的发展脉络，探讨新加坡设置及终止《宗教知识》的原因。而虽有学者对《宗教知识》一课做了概括性的研究，但是课程教育潜能与学生各自的学习经验却未获得任何关注。故为了分析课程的有效性，本文将以《佛学》作为研究个案，着手分析课本内容，以助了解佛教与培养道德价值观的关系。同时，本文将针对当时修读《佛学》学生的亲身经历和看法进行问卷调查，并对研究新加坡佛教发展史的许源泰博士进行访谈。在课文分析的基础上，本文亦将所得数据和见解中深入分析《佛学》对道德培养的有效性，从而对《佛学》培养人民素质给予评论。Since her independence in 1965, the government of Singapore was tasked with an extremely rigorous challenge of building a nation, with its traditions and cultures challenged by the onset of modernization. The main goal was then to steer away from the tumultuous times and create a sense of national identity upon which people of different ethnic background could co-exist harmoniously without prejudice and discrimination. Education was seen as the optimal way for Character and Citizenship Education, with its priorities aimed at producing a morally upright citizenry. It was the year 1984 when the government implemented Religious Knowledge (RK) as its new moral education module, which aimed to utilise religious teaching as a moral guide for code of conduct. However, RK only lasted for six years before its abolishment from the education system. To the aforementioned, I would first explore the reasons behind the implementation and dismissal of RK. While there were discussions on the introduction and withdrawal of RK, no attention was given with regards to its educational potential and the experiences individual students had of RK. Hence, in order to analyse the effectiveness of RK on cultivating moral values, I would then expand into the second and third part, in reference to Buddhist Studies as my case study, focusing on examining the content of its textbook. This acts as a preface to understand how religious teaching is related to educating moral values. At the same time, I have also interviewed Professor Hue Guan Thye, who is a well-known researcher in the history of Singapore Buddhism, and designed a questionnaire to seek the views of students who had studied Buddhist Studies back in the Eighties. Finally, based on the results and views collected, I would analyse the effectiveness of Buddhist Studies on cultivating moral values, before giving critique on its impact on producing morally upright citizenry.